KEEFEKTIFAN PERMAINAN SUGOROKU (ULAR TANGGA) DALAM PEMBELAJARAN KOSAKATA BAHASA JEPANG (Penelitian Kuasi Eksperimen Terhadap Siswa SMK KANSAI Pekanbaru) - Indah Risti Fauzi; Sri Wahyu Widiati; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study discusses the game sugoroku (snakes and ladders) in learning Japanese vocabulary to vocational students KANSAI Pekanbaru. The purpose of this study was to determine significant differences between the vocabulary of students who use the games sugoroku and who do not use sugoroku games, as well as how the vocabulary before and after implementation of sugoroku game.The object of research is a class XII student of SMK KANSAI Pekanbaru first semester, 2016/2017 academic year consisting of two classes, namely class XII and XII Tekhknik Accounting Information. This study is a quasi-experimental research.A quasi-experimental design used in this study is a pretest-posttest design, committed against two classes, namely class experimental and control classes.Results of the study found that the game sugoroku (snakes and ladders) can improve learning outcomes Japanese vocabulary compared with the results of student learning vocabulary with the conventional method (memorizing). It can be seen from the results of the evaluation and the difference between pretest and posstets experimental class (class treatment) are also increasing, with 82.75 to the average value in the experimental class and 60 in the control class.Keywords : Learning Vocabulary, Games Sugoroku, SMK Students KANSAI Pekanbaru.